(3OjhGf HgQGe TGgs - (3HgQGe TGg Hf aQhN TGg Hf TGgfTGg Hf CjhH Hf TGOj,Gdedc GdCeLO GdeXaQ , J (B628 (3g` s ((3GdOjQj Hf CHj GdHbGA GdOjQj s)
(3ChdgG (B:s
(3dehdGfG GdSdWGf GdCLd eeG fXeg aj GdfSjH hGdJZRd hGdMeGSI aj eOI ChdgG TgQ QeVGf GdeYXe s
(3BNQgG (B:s
(3OfG LjO gPG GdOgQ efg hWGdeG ZPG YGWdkG ef bHd TYQj aMdGg s
(3fSNI KGdKIs
(3jdjgG eLehYI bUGFO dHYV GdoaVdGAs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B81s
Keywords: (3GdCOHs